2013
DOI: 10.1182/blood-2013-04-496448
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive mutational profiling in advanced systemic mastocytosis

Abstract: Key Points Additional genetic aberrations apart from KIT D816V are found in advanced systemic mastocytosis. Additional genetic aberrations apart from KIT D816V are associated with a significant reduction of overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
242
0
8

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 229 publications
(259 citation statements)
references
References 40 publications
9
242
0
8
Order By: Relevance
“…In any case, additional lesions and hits may have been responsible for progression to chronic MCL and from chronic MCL into acute MCL. Indeed, several molecular lesions have recently been associated with a more aggressive course of SM [41,42]. However, although we screened for several known mutations we were unable to detect another driver lesion responsible for disease evolution.…”
Section: Discussionmentioning
confidence: 86%
“…In any case, additional lesions and hits may have been responsible for progression to chronic MCL and from chronic MCL into acute MCL. Indeed, several molecular lesions have recently been associated with a more aggressive course of SM [41,42]. However, although we screened for several known mutations we were unable to detect another driver lesion responsible for disease evolution.…”
Section: Discussionmentioning
confidence: 86%
“…6 Nextgeneration deep amplicon sequencing by 454 FLX amplicon chemistry (Roche, Penzberg, Germany) was performed to investigate 18 genes recurrently mutated in myeloid neoplasms as previously described. 9 …”
Section: Gene Mutation Analysesmentioning
confidence: 99%
“…6,7 The multi-lineage expansion by KIT D816V and the KIT D816V allele burden (AB) have an important impact on disease phenotype and prognosis. 6,[8][9][10] Furthermore, the presence and number of molecular aberrations, e.g. in SRSF2, ASXL, or RUNX1 (S/A/R gene panel), have a strong adverse impact on disease phenotype and OS in patients with advSM.. 9,11 One of several WHO criteria to classify SM includes enlargement of visceral organs, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing number of cases diagnosed with SM at least partly reflects the development of standardized diagnostic, classification and treatment-response criteria by international collaborative organizations such as the World Health Organization (WHO) and European Competence Network on Mastocytosis (ECNM) [4][5][6]. Prior to these larger-scale projects, most SM related data emerged from single center or single country registry studies, which despite their inherent limitations helped establish the early foundational principles of SM evaluation and treatment [7][8][9][10][11][12][13]. The article by Pieri et al in the current issue of the American Journal of Hematology represents a large study of SM patients from 10 Italian centers with dedicated mastocytosis programs participating in the Italian Registry of Mastocytosis [14].…”
mentioning
confidence: 99%
“…The survival analysis is further limited by the fact that detailed molecular findings were not reported. Recent studies have demonstrated adverse survival outcomes in SM patients harboring mutations in specific genes (e.g., ASXL1, SRSF2) [10,20].…”
mentioning
confidence: 99%